Are casualties from mass-casualty Motor Vehicle Crashes different from casualties of other Motor Vehicle Crashes?. (December 2020) - Bodas, Moran; Givon, Adi; Peleg, Kobi; ,; Abbod, N.; Bahouth, H.; Bala, M.; Becker, A.; Ben Eli, M.; Braslavsky, A.; Grevtsev, I.; Jeroukhimov, I.; et al.
Abstract: Introduction: Mass Casualty Incidents (MCI) by Motor Vehicle Crashes (MVCs) are most common type of MCIs. Casualties from MCIs usually require more hospitalization resources. The purpose of this study was to compare the injury characteristics, survivability, and medical resource utilization of casualties from Mass-Casualty Motor Vehicle Crashes (MC-MVCs) and casualties from other (non MCI) MVCs. Methods: This retrospective cohort study examined a population of 50, 321 Israeli casualties hospitalized due to MVCs between 1998 and 2017, of which 595 (1.2%) were admitted from a MC-MVC. Analysis included type of motor vehicle involved and collision circumstances, injury characteristics, hospital resource utilization, and demographics. Results: The results suggest that most casualties from MC-MVCs were bus passengers who were injured when the vehicle rolled over. Injuries from MC-MVCs were more urgent as almost two times more MC-MVCs casualties were rushed directly from the emergency room into the operating rooms and intensive care units than casualties of regular MVCs. Mortality rate was higher in MC-MVCs compared to regular MVCs (2.69% compared to 1.46%, respectively; p = .013). Severe injuries (ISS≥16) were more frequent in MC-MVCs (23.40% versus 15.53%, p < .0001). Casualties from MC-MVCs required more hospitalization resources, including ICU admission, surgery, and extended lengths of stay. The multivariate analysis demonstrated that mass casualty conditions are predictive of severe injuries even when controlling for age, gender, and collision circumstances. Conclusions: This study demonstrates that hospitals receiving casualties from MC-MVCs should expect not only a multitude of casualties, rather also the need to treat more urgent and severe injuries, in more body regions per casualty, and expect higher admissions rates to intensive care units and operation rooms under MCI conditions. Highlights: Injuries from Mass Casualty Motor Vehicle Crashes (MC-MVC) were more urgent. Mortality rates of casualties from MC-MVCs were higher compared to other MVCs. Hospitals receiving MC-MVCs' casualties should expect to treat more severe injuries. Hospitals can expect higher admissions rates to intensive care and operation rooms.